1978
DOI: 10.1111/j.1365-3083.1978.tb00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Functional Characteristics of Peripheral Blood and Synovial Fluid Lymphocytes from Patients with Rheumatoid Arthritis

Abstract: Spontaneous (SCMC) and antibody dependent cellular cytotoxicity (ADCC); mitogenic responsiveness (PHA, Con A, PPD, dextran and pokeweed) as well as lymphocyte subpopulations (E‐, EA‐, EAC‐rosettes, S‐Ig) were studied simultaneously in peripheral blood (PBL) and synovial fluid lymphocytes (SFL) of fifteen patients with rheumatoid arthritis. Marked differences were observed in the cytotoxic activity of SFL and PBL. Whereas SCMC activity of SFL was always significantly elevated above the cytotoxic levels of PBL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…Burmester (18) reported slightly reduced spontaneous cytotoxicity of blood lymphocytes against a melanoma cell line (IGR3) in subjects with RA, but only at effector-to-target ratio of 100: 1, a ratio considerably above the 20: used in the present studies. Our finding that lymphocyte ADCC is normal in RA is in agreement with several other reports (18)(19)(20). Only Isturiz and coworkers (21) have reported decreased lymphocyte ADCC in RA.…”
Section: Discussionsupporting
confidence: 83%
“…Burmester (18) reported slightly reduced spontaneous cytotoxicity of blood lymphocytes against a melanoma cell line (IGR3) in subjects with RA, but only at effector-to-target ratio of 100: 1, a ratio considerably above the 20: used in the present studies. Our finding that lymphocyte ADCC is normal in RA is in agreement with several other reports (18)(19)(20). Only Isturiz and coworkers (21) have reported decreased lymphocyte ADCC in RA.…”
Section: Discussionsupporting
confidence: 83%
“…The presence of Interferon-y has been documented both in the rheumatoid synovium (32) and the synovial fluid (33). A possible source of this mediator may be the large number of activated Ia' T cells present in this compartment (13,27,34), especially in view of the finding that Ia' T cells are the primary producers of Interferon-'y in in vitro assays (35). (39), on keratinocytes in lichen ruber planus (40), and on other cell types in various autoimmune diseases (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the monoclonal anti-Ia reagents are outlined in Table I (26]), whereas B cells were detected by surface immunoglobulin staining (27). All the reagents described above were used in concentrations that had been shown in extensive preliminary studies to be saturating using the fluorescence-activated cell sorter.…”
Section: Methodsmentioning
confidence: 99%
“…detectable infectious agents, large numbers of T lymphocytes, including the CD4+ T helperiinducer cell subset, infiltrate the synovium (1,2). Several studies have demonstrated an activated phenotype and altered functional properties of these cells (3,4). Moreover, in animal models, arthritis is inducible in healthy animals solely by the injection of arthritogenic T cell clones or lines (5).…”
mentioning
confidence: 99%